Experimental evaluation of atmospheric plasma treatment effects on different textures of CFRP composite for aircraft applications - Alkoc, Ahmetcan; Yoruc, Afife Binnaz Hazar; Bakir, Mete; Usak, Adem Can (TAYLOR & FRANCIS LTD, 2024)
This article examines the impact of Atmospheric Plasma Treatment (APL) on the chemical composition and fracture properties of various textured surfaces (tool and bag side) of carbon fiber/epoxy (CFRP) composites utilized in aircraft applications. For this purpose, parameters of atmospheric plasma (APL) surface treatment were evaluated in comparison to chemical cleaning and peel-ply applications, taking into account its effects on surface properties and adhesive bond strength. A comprehensive variety of surface characterization techniques were utilized to analyze surface modifications, including water and diiodomethane contact angle measurements for assessing surface hydrophilicity, Fourier Transform Infrared Spectroscopy with Attenuated Total Reflection (FTIR-ATR) and X-ray Photoelectron Spectroscopy (XPS) for analyzing chemical composition and functional groups, and Profilometry, Atomic Force Microscopy (AFM), and Scanning Electron Microscopy (SEM) for evaluating surface topography and morphology. Experimental results indicated that the reduction in the contact angle following plasma treatment correlated with the elevated oxygen concentration and the presence of polar functional groups (e.g. -OH, -NH2, -NH3, C=O, O-C=O) on the composite surface. Plasma treatment, especially at low nozzle speeds, increased surface roughness on the bag side surfaces. This prevented adhesive penetration and led to gas entrapment, resulting in adhesive failure mode and reduced single lap shear strength for the bag side. In contrast, on the tool side surfaces, the plasma treatment led to a remarkable 19.7% enhancement in shear strength, highlighting its effectiveness.
Keywords: Aircraft composites; surface treatment; atmospheric plasma; adhesion by chemical bonding; X-ray photoelectron spectroscopy; SURFACE-TREATMENT; JOINTS; FUNCTIONALIZATION; CHEMISTRY; BEHAVIOR; Materials Science